Gender Role and Family Pattern in Kerala - Thomas, Dr. Laisa (International Journal of Scientific Research and Management (IJSRM), 2017)
The most important determinants of family size are family structure and fertility. A wide change in the perception towards family has occurred in the minds of people of Kerala. Through demographic transition and the influence of Western culture, the traditional values have been greatly modified. The credit of positive trend observed in Kerala is due to the uniqueness of its culture evolved through the ages. One of the striking and most impressive changes that have taken place in the state during the last three decades is the decline in fertility. In the present context, a study was carried out among the women to analyse the factors that determine family size and the role of gender difference in it. From the study it is seen that the major family planning decisions were taken by the age of ‘35’. It is seen that in old-age, parents give more importance to physical security than financial security.